Light Sandy Beaches Favour Hatching Success and Best Hatchling Phenotype of Loggerhead Turtles - Patino-Martinez, Juan; Veiga, Jairson; Afonso, Inês O.; Yeoman, Kate; Mangas-Viñuela, José; Charles, Gemma (Frontiers in Ecology and Evolution, 2022)
We conducted a five-year field (2017-2021) and laboratory study of the relationship between type of substrate and hatching success, embryonic development, and the quality of hatchlings in loggerhead turtle nests. Our study site, the island of Maio in the archipelago of Cabo Verde, one of the world’s largest loggerhead turtle nesting colonies, displays marked heterogeneity of sand coloration, with dark, mixed, and light sandy beaches. We experimentally incubated eggs, comparing different nesting substrates under standard temperature and humidity conditions. Females nest in all sand types without preference. However, both the field and experimental study revealed a significant difference in hatching success depending on the type of substrate. Substrate of volcanic origin, dark in colour, with a lower amount of calcium carbonate, had an average hatching success (HS) of 30.3 ± 20.2%, producing higher and earlier embryo mortality than substrates of mixed (HS = 46.1 ± 26.5%) or light (HS = 78.1 ± 18.2%) colour. Conversely, eggs experimentally incubated in substrate that was light-coloured, with a larger grain size and higher calcium carbonate concentration, produced significantly more and larger offspring. Incubation temperatures were significantly higher in dark substrate, which partially explains the lower hatching success in this type of sand. However, experimental incubation with controlled temperatures consistently showed lower hatching success in dark sand. Thus, we found that not only the temperature, but also the specific characteristics of each substrate determine hatching success. The main predator of eggs and hatchlings (the ghost crab Ocypode cursor) showed no significant differences in abundance or size between different substrate types. Our results indicate that nest site selection between beaches or even within the same beach with different substrate conditions affects hatching success, hatchling physical condition and subsequently the reproductive success of each female. The results of this study can inform conservation programs with nest management and controlled incubation in the field and optimise adaptive nest management under future scenarios of rising global temperatures.